CORPORATE GOVERNANCE APPLIED TO SMALL AND MEDIUM-SIZED ENTERPRISES: LIMITATIONS OF TRADITIONAL MODELS AND ADAPTATION PROPOSALS - Rizzo Rocha, Rafael (Revista Gênero e Interdisciplinaridade, 2026)
This article examines, through a systematic literature review, the application of corporate governance practices in small and medium-sized enterprises (SMEs). The investigation focuses  on  scientific  production  from  the  last  five  years,  seeking  to  understand  the inherent limitations of traditional governance models — originally designed to meet the demands of large publicly traded corporations — and to map the adaptation alternatives being developed by the academic community. The research was conducted through a structured  search  in  Scopus,  Web  of  Science,  SciELO,  and  Google  Scholar  databases, employing qualitative analysis of the selected works. The findings reveal that, although the adoption of formal governance mechanisms in SMEs is still in an embryonic stage, the implementation  of  adapted  practices  —  notably  the  promotion  of  transparency,  the establishment of accountability mechanisms, and the constitution of advisory boards — produces significant positive effects. Such practices not only expand the possibilities for raising  financial  resources  but  also  enhance  innovative  capacity,  strengthen organizational  resilience,  and  increase  the  competitiveness  of  these  companies.  The conclusion points to the absence of a universal governance model applicable to SMEs, making  it  essential  to  adopt  flexible  and  gradual  approaches  that  consider  the specificities of this business segment: ownership concentration, the lack of distinction between  management  and  ownership,  family  ties,  and  resource  constraints.  Future investigations should prioritize longitudinal studies and behavioral analyses of the actors involved in governance processes.